Who attains balance? A comparative study of work–life reconciliation across demographics - Salehi, Ali; Tremblay, Diane-Gabrielle (American Journal of Social Sciences and Humanities, 2026)
This study examines work–life reconciliation (WLR) among employees in Québec, analyzing how individual characteristics, socio-economic resources, and institutional supports shape experiences of balance across three dimensions: work schedule and time flexibility, organizational and social support, and perceived work–family compatibility. Using survey data collected from a family-oriented network in Quebec, we find that overall levels of reconciliation are moderate to moderately high, with modest differences across gender, age, education, and income. Women report slightly lower perceived compatibility, younger employees show lower reconciliation than mid- or late-career workers, and higher education and income are associated with incremental advantages. These patterns indicate that WLR is influenced by cumulative resources and structural conditions rather than individual effort alone. Québec’s policy framework, including publicly funded childcare, parental leave, and family-friendly employment standards, appears to moderate extreme inequalities, though subtle socio-demographic gradients persist. Building on these results, we propose a contextually embedded model of WLR, highlighting the dynamic interaction between individual characteristics, socio-economic position, and institutional environment. This framework integrates stratification, life-course, and resource perspectives, providing a novel lens for understanding both opportunities and constraints in achieving work–life balance. The study offers insights for policy and organizational design, particularly in supporting early-career and lower-resource employees, while advancing theoretical understanding of multidimensional reconciliation.